The Dancing Plague - Book 2 - Bates, Jeremy ([United States?] : Ghillinnein Books, 2022)
In the sixteenth century, hundreds of residents of Strasbourg in Alsace (now France) danced uncontrollably for days on end, many dropping dead from their exertions. Nearly four hundred years later, the "dancing plague" has returned, this time afflicting the residents of an idyllic Cape Cod town. For twelve-year-old Ben Graves and his two friends, the inexplicable dancing mania is only the beginning of the horror to come.
Keywords: Werewolves -- Fiction; Chorea, Epidemic -- Fiction; Cape Cod (Mass.) -- Fiction; Bildungsromans; Horror fiction